“Bordeaux Neobladder”: First Evaluation of the Urodynamic Outcomes - Anastasios D. Asimakopoulos; Marilena Gubbiotti; Enrico Finazzi Agrò; Elena Morini; Valentina Giommoni; Thierry Piechaud; Richard Gaston; Filippo Annino (European Urology Open Science, 2023)
Background: The intracorporeal orthotopic modified-Y “Bordeaux“ neobladder (iYNB) was first described in 2016. No urodynamic evaluation of this neobladder has yet been performed. Objective: To present the urodynamic features of the iYNB and incontinence-specific health-related quality of life (HRQoL) outcomes. Design, setting, and participants: We prospectively assessed 26 patients operated between September 2018 and November 2020. Surgical procedure: Robotic radical cystectomy for malignant disease of the bladder and iYNB, performed by a single surgeon, were used. Measurements: Three months after surgery and in November 2021, consenting patients underwent clinical evaluation and multichannel urodynamic study (UDS). The incontinence quality of life (I-QoL) questionnaire was used to evaluate HRQoL. Continence was classified into day- and nighttime, and clinically defined as the use of zero pads. A descriptive statistical analysis was performed. Results and limitations: The mean age at surgery was 65.4 yr. The mean follow-up period was 27 mo (12–38). The mean time for the neobladder reconstruction was 192 min (110–340). The mean maximum capacity was 431 cm3 (range 200–553). The mean postvoid residual was 101.6 ml (0–310), and the rate of clean intermittent catheterization was 17.6%. With the exception of a significant reduction in the volume of the first sensation of bladder fullness, no other statistically significant changes in the UDS parameters of both the storage and the voiding phase were observed over time. Day- and nighttime continence rates were 58.8% and 23.5%, respectively. The mean postoperative I-QoL score was 103.3 (89–110). Limitations include the small number of patients and short follow-up. Conclusions: The UDS evaluation of iYNB demonstrates that both the volumetric and the pressure characteristics are acceptable and may enhance quality of life. Prospective studies with larger numbers of patients and longer follow-up are needed to further evaluate the iYNB. Patient summary: The “Bordeaux“ neobladder provides acceptable urodynamic outcomes. It is associated with high levels of health-related quality of life and good rates of continence in patients.